2021
DOI: 10.48550/arxiv.2111.04778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shocks in the Stacked Sunyaev-Zel'dovich Profiles of Clusters II: Measurements from SPT-SZ + Planck Compton-y Map

D. Anbajagane,
C. Chang,
B. Jain
et al.

Abstract: We search for the signature of shocks in stacked gas pressure profiles of galaxy clusters using data from the South Pole Telescope (SPT). Specifically, we stack the recently released Compton-𝑦 maps from the 2500 deg 2 SPT-SZ survey on the locations of clusters identified in that same dataset. The sample contains 516 clusters with mean mass 𝑀 200m = 10 14.9 M and redshift 𝑧 = 0.55. We analyze in parallel a set of zoom-in hydrodynamical simulations from T T H project. The SPT-SZ data show two features: (i) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 131 publications
1
10
0
Order By: Relevance
“…The outskirts of the mean dark matter and gas density profiles in massive halos have received significant attention in recent times from both theory and observations (Walker et al 2019, and references therein), and can serve as probes of astrophysics and of cosmological structure formation (e.g., Aung et al 2021;Anbajagane et al 2021, for recent works). In the bottom panels of Figure 2, we see that in the cluster core the dark matter density profile has the least scatter of the three profiles, by about a factor of 2 or more.…”
Section: Resultsmentioning
confidence: 99%
“…The outskirts of the mean dark matter and gas density profiles in massive halos have received significant attention in recent times from both theory and observations (Walker et al 2019, and references therein), and can serve as probes of astrophysics and of cosmological structure formation (e.g., Aung et al 2021;Anbajagane et al 2021, for recent works). In the bottom panels of Figure 2, we see that in the cluster core the dark matter density profile has the least scatter of the three profiles, by about a factor of 2 or more.…”
Section: Resultsmentioning
confidence: 99%
“…As one can see, the simulated profile matches the observed one well at ΞΈ < 50 arcmins, corresponding to about 0.7 times the virial radius, but is lower around the virial radius. Recently, Anbajagane et al (2021) analyzed the SZ data of several hundred clusters and compared the results with simulations (Cui et al 2018). They found that the average profile of the simulated clusters is also lower than the observation outside the virial radius.…”
Section: The Thermal Sz Effectmentioning
confidence: 99%
“…A more detailed introduction of The Three Hundred can be found in Cui et al (2018). Besides these studies on the cluster dynamical state which has been mentioned in the introduction, these simulated galaxy clusters have been used for different proposes: the filaments around the clusters (Rost et al 2021;Kuchner et al 2020Kuchner et al , 2021Kotecha et al 2021); the backsplash galaxies (Haggar et al 2020;Knebe et al 2020) and shock radius (Baxter et al 2021;Anbajagane et al 2021b). The advanced baryon models in hydrodynamic simulations allow us to perform a detailed investigation on the cluster properties, such as profiles (Mostoghiu et al 2019;Li et al 2020), substructure and its baryonic content (Arthur et al 2019;Haggar et al 2021;Mostoghiu et al 2021b,a), the cluster (non-)thermalization (Sayers et al 2021;Sereno et al 2021), the fundamental plane (DΓ­az-GarcΓ­a et al 2021), and the cluster mass bias (Ansarifard et al 2020;Li et al 2021;Anbajagane et al 2021a).…”
Section: The Three Hundred Projectmentioning
confidence: 99%